(untitled) (Journal on Excellence in College Teaching, 2024)
Flash writing–short narratives of less than 2000 words–is extremely popular these days. This essay describes a multi-genre course designed to introduce undergraduate students to a genre they will undoubtedly find appealing. Although the primary focus of the course is on creative writing, a great deal of emphasis is placed on literary analysis. Over the course of the semester, students produce pieces written in a variety of styles and forms and take an exam that tests their knowledge of the literature. This essay argues that students who study and produce such work are able to hone critical thinking skills in ways they never thought possible. The brief works are not only more appealing to readers and writers in the Internet age, but they also provide students with an unprecedented understanding of the value of every single word.